2016
DOI: 10.18203/2320-1770.ijrcog20160383
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of pregnant women regarding anemia, iron rich diet and iron supplements and its impact on their hemoglobin levels

Abstract: Background: Anemia in pregnancy has detrimental effects on maternal and child health and prevalence of anemia during pregnancy is alarmingly high, inspite of the implementation of the national nutritional anemia prophylaxis programme which provides iron and folic acid which are the essential nutrients lacking in their diet. The purpose of this study was to assess the knowledge, attitude and practices of pregnant women regarding anemia, Iron rich food and iron supplements and also to assess the impact of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
1
1
Order By: Relevance
“…On the other hand, our results were not in accordance with many previous works, Nivedita & Shanthini (2016) showed that only 39% of the women participated in their study showed good knowledge regarding the term anemia and generally women reported low level of knowledge. Yadav et al (2014) also reported lack of knowledge regarding iron deficiency anemia among women in their study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our results were not in accordance with many previous works, Nivedita & Shanthini (2016) showed that only 39% of the women participated in their study showed good knowledge regarding the term anemia and generally women reported low level of knowledge. Yadav et al (2014) also reported lack of knowledge regarding iron deficiency anemia among women in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…More so, this condition is thought to be the most common cause of anemia globally, but some other nutritional deficiencies (including folate, vitamin B12 and vitamin A), acute and chronic inflammation, parasitic infections, and inherited or acquired disorders can cause anemia as well (Lokeshwar et al 2011). Anemia can lead to some complications and risks for the pregnant women and the fetus that include increased risk of premature delivery, low birth weight babies, inadequate iron stores in the newborn, and increased risk of morbidity and mortality in perinatal and neonatal period and among pregnant females (Nivedita & Shanthini 2016). There have been few research studies on the epidemiology of IDA in pregnancy in Arab countries.…”
Section: Introductionmentioning
confidence: 99%